2015
DOI: 10.1016/j.bjid.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Membranous glomerulonephritis secondary to syphilis

Abstract: A 57-year-old man presented with bilateral leg swelling, myal-gia, weight gain, and reduced urine output for three months. He exhibited no signs and symptoms of urinary tract infection or sexually transmitted disease (STD). He reported a past medical history of diabetes mellitus and hypertension for 20 years, and bariatric surgery and abdominoplasty from about five years ago. Blood cell count was normal. Serum creati-nine and creatinine clearance were 1.9 mg/dL and 49 mL/min, respectively. A 24-h urine collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…1 MN is the most common cause of nephrotic syndrome in syphilis, although it has been reported in only small series or case reports. [4][5][6][7][8][9] MN is characterized by accumulation of immune complexes in the subepithelial region along glomerular basement membranes (GBM). [10][11][12] MN is often classified into primary MN, where there is no identifiable underlying disease association, and secondary MN, where MN may be associated with an autoimmune disease, infections such as hepatitis and syphilis, malignancy, hematopoietic stem cell transplant, drugs, etc.…”
Section: Introductionmentioning
confidence: 99%
“…1 MN is the most common cause of nephrotic syndrome in syphilis, although it has been reported in only small series or case reports. [4][5][6][7][8][9] MN is characterized by accumulation of immune complexes in the subepithelial region along glomerular basement membranes (GBM). [10][11][12] MN is often classified into primary MN, where there is no identifiable underlying disease association, and secondary MN, where MN may be associated with an autoimmune disease, infections such as hepatitis and syphilis, malignancy, hematopoietic stem cell transplant, drugs, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection caused by Treponema pallidum . Proteinuria in congenital and acquired latent (secondary or tertiary) syphilis has been mostly associated with membranous nephropathy (MN) [ 1 ]. The 10 MN patients in the present study had venereal disease research laboratory positivity confirmed with fluorescent treponemal antibody absorbed after the biopsy diagnosis.…”
mentioning
confidence: 99%